Using NCL to Synchronize Media Objects, Sensors and Actuators - Guedes, Álan L. V.; Cunha, Marcio; Fuks, Hugo; Colcher, Sergio; Barbosa, Simone D.J (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
IoT (Internet of Things) technologies are underway. Both industry and academia have been proposing technologies to support IoT. In particular, some IoT scenarios include audio-video data and aims at integrating multimedia content and IoT technologies. In this paper, we investigate the support for those scenarios through a multimedia language. More precisely, we use NCL (Nested Context Language) to take advantage of IoT devices and to specify interactive multimedia applications synchronizing sensors and actuators, besides the media objects. To help evaluate our approach, we present a usage scenario using an NCL application that synchronizes media objects and IoT devices.